Agroecological transition in wetland livestock systems in Argentina: effects on grasslands and soil physicochemical properties - Muchiutti, Ayelén Andrea (2026)
Wetlands provide a wide range of essential ecosystem goods and services for humanity. However, various anthropogenic activities, including overgrazing, have degraded these ecosystems, threatening their integrity. Consequently, it is crucial to develop sustainable strategies to ensure their long-term conservation. In this context, agroecology, as a framework guiding agroecological transition, offers a viable alternative, providing strategies and tools for the sustainable management of productive systems. This study evaluates the association between agroecological transition stages and two key components within extensive livestock systems in minimally disturbed wetlands of central Argentina: (1) grassland plant attributes and (2) soil physicochemical properties. Nine ranches were evaluated, representing a different stage of agroecological transition: non-agroecological ranches (NAR), transitional ranches (TR), and advanced agroecological ranches (AAR). The findings reveal that AAR exhibited greater forage species richness, greater perennial and legume cover, and a lower proportion of bare soil. Regarding soil characteristics, AAR showed lower Bd, higher N tot, NH4+, NO3−, and P ex. compared to NAR. Overall, the results underscore the potential of agroecological approaches to improve both vegetation structure and soil health, contributing to the ecological sustainability and resilience of wetland-based livestock systems under ongoing environmental pressures.